The implementation of Geography learning with spatial representation using the discrepancy evaluation model - Nursa'ban, Muhammad; Mukminan, Mukminan (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2023)
This study aims to evaluate the learning process of geography with spatial representation in high school using the Discrepancy Evaluation Model (DEM) from Provus. Evaluation goes through five stages: design, installation, process, and product, as well as implementation comparison. Respondents were five teachers and 208 students from SMA 1 Srandakan, MAN 2 Yogyakarta, and SMA 1 Pundong in Yogyakarta. The evaluation was carried out in February-July 2021. The focus of the evaluation includes (1) learning design, (2) learning tools, (3) learning implementation, (4) learning outcomes, geographic critical thinking, and (5) implementing learning comparisons. Data were collected through document studies, observations, tests, and questionnaires. Descriptive analysis was used to measure gaps in each stage and efforts to improve them, while experimental quantitative analysis was used to compare learning. The DEM results describe gap variations in stages 1-4. However, in collaborative improvement efforts at stages 1-3, there is an increase in spatial critical thinking skills. The test results at stage 5, learning geography with spatial representations, are more effective for improving students' spatial critical thinking skills than textbook-oriented learning and media images. Recommendations on the results of the evaluation at all stages for organizing geography learning with spatial representation: (1) strengthening understanding and mentoring of the concept of spatial representation and learning design, (2) monitoring and periodic testing of geography learning with spatial representation to improve critical thinking skills in geography.